TRADE AND GLOBALIZATION - DEEPAK NAYYAR (NEW DELHI OXFORD UNIVERSITY PRESS, 2008)
This collection of fifteen essays by eminent economist Deepak Nayyar provides an unusual blend of theory and policy, of applied research and empirical work, and of the world economy and India.
Keywords: INTERNATIONAL TRADE; GLOBALIZATION-ECONOMIC ASPECTS